Disparate response of articular- and auricular-derived chondrocytes to oxygen tension. (3rd July 2016) - Kean, Thomas J.; Mera, Hisashi; Whitney, G. Adam; MacKay, Danielle L.; Awadallah, Amad; Fernandes, Russell J.; Dennis, James E.
ABSTRACT: Purpose/Aim: To determine the effect of reduced (5%) oxygen tension on chondrogenesis of auricular-derived chondrocytes. Currently, many cell and tissue culture experiments are performed at 20% oxygen with 5% carbon dioxide. Few cells in the body are subjected to this supra-physiological oxygen tension. Chondrocytes and their mesenchymal progenitors are widely reported to have greater chondrogenic expression when cultured at low, more physiological, oxygen tension (1–7%). Although generally accepted, there is still some controversy, and different culture methods, species, and outcome metrics cloud the field. These results are, however, articular chondrocyte biased and have not been reported for auricular-derived chondrocytes. Materials and Methods: Auricular and articular chondrocytes were isolated from skeletally mature New Zealand White rabbits, expanded in culture and differentiated in high density cultures with serum-free chondrogenic media. Cartilage tissue derived from aggregate cultures or from the tissue engineered sheets were assessed for biomechanical, glycosaminoglycan, collagen, collagen cross-links, and lysyl oxidase activity and expression. Results: Our studies show increased proliferation rates for both auricular and articular chondrocytes at low (5%) O2 versus standard (20%) O2 . In our scaffold-free chondrogenic cultures, low O2 was found to increase articular chondrocyte accumulation of glycosaminoglycan, but not cross-linked type II collagen, or total collagen. Conversely, auricular chondrocytes accumulated less glycosaminoglycan, cross-linked type II collagen and total collagen under low oxygen tension. Conclusions: This study highlights the dramatic difference in response to low O2 of chondrocytes isolated from different anatomical sites. Low O2 is beneficial for articular-derived chondrogenesis but detrimental for auricular-derived chondrogenesis.